Synchrotron X-ray tomography reveals a new genus of tropiduchid planthopper (Hemiptera: Fulgoromorpha) from Eocene Baltic amber - Boderau, Mathieu; Peng, Ancheng; Jouault, Corentin; Nel, Andre (Zootaxa, 2025)
We describe a new genus and species of the small planthopper family Tropiduchidae Stål, 1866, Discotropiduchus junoi gen. et sp. nov. This new taxon highlights the remarkable diversity of tropiduchid planthoppers preserved in Eocene Baltic amber. Moreover, its morphological characters are incompatible with any currently recognized tropiduchid tribe. We therefore discuss the affinities of the new genus with the tribes previously established within Tropiduchidae.